Height of the Fractured Zone in Coal Mining under Extra-Thick Coal Seam Geological Conditions. (11th August 2021) - Sun, Dequan; Li, Xiaoyan; Zhu, Zhijie; Li, Yang; Cui, Fang
Abstract : The height of the fractured zone caused by coal mining is extremely significant for safely mining under water, water conservation, and gas treatment. At present, the common prediction methods of overburden fractured zone height are only applicable to thin and medium-thick coal seams, not suitable for thick and extra-thick coal seams. In order to determine the overburden fractured zone distribution characteristics of extra-thick seam mining, failure process analysis method of overlying strata was proposed based on key strata theory. This method was applied to 15 m coal seam of Tongxin coal mine, and fractured zone height was determined to be 174 m for 8100 panel. EH4 electromagnetic image system and borehole televiewer survey were also conducted to verify the theory results. The distribution of the electrical conductivity showed that the failure height was 150–170 m. Observation through the borehole televiewer showed that the fractured zone height was 171 m. The results of the two field test methods showed that the fractured zone height was 150–171 m, and it was consistent with the theory calculation results. Therefore, this failure process analysis method of overlying strata can be safely used for other coal mines.